2006
DOI: 10.1007/s00213-006-0428-x
|View full text |Cite
|
Sign up to set email alerts
|

The neurocognitive effects of aripiprazole: an open-label comparison with olanzapine

Abstract: The findings from this open-label study suggest that the neurocognitive effects of aripiprazole are at least as good as those of olanzapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 40 publications
(26 reference statements)
11
48
3
2
Order By: Relevance
“…All the AEs were also of mild to moderate severity. The reported AEs (akathisia, insomnia, agitation, sedation and depression) were in keeping with the most common adverse effects found in other clinical trials of aripiprazole in schizophrenia [38,39]. There was a non-significant increase in BARS, mainly due to four patients who reported akathisia.…”
Section: Discussionsupporting
confidence: 84%
“…All the AEs were also of mild to moderate severity. The reported AEs (akathisia, insomnia, agitation, sedation and depression) were in keeping with the most common adverse effects found in other clinical trials of aripiprazole in schizophrenia [38,39]. There was a non-significant increase in BARS, mainly due to four patients who reported akathisia.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are in accordance with studies that have shown that atypical antipsychotics may improve cognitive tasks [2,6] . Aripiprazole decreased baseline DNA damage in brain tissue, which suggests a neuroprotective effect, and no cytotoxic or mutagenic effects were detected.…”
Section: Lipoperoxidationsupporting
confidence: 93%
“…Similarly, some investigations have evaluated the effect of antipsychotic drugs on cognitive parameters in humans and animals [4,5] . Research suggests that schizophrenic patients treated with atypical antipsychotics may perform better in cognitive tasks when compared to patients treated with typical antipsychotics [2,6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain imaging studies in schizophrenia patients have shown that AMPH-induced DA release is enhanced in the STR (78) (hyperdopaminergia), whereas a recent study has shown, for the first time, cortical hypodopaminergia in schizophrenia patients (79). Partial agonists, such as ARI, were originally developed to counteract these opposite phenomena but have largely been unsuccessful in correcting cortical dysfunction (80,81). Our behavioral and electrophysiological data show that the ARI-derived βarr2-biased D2R ligand, 94A, can act as a D2R-βarr2 agonist in the PFC but a D2R-βarr2 antagonist on striatal D2 MSNs, highlighting the feasibility of a pharmacological approach, where a drug could potentially simultaneously counteract both the cortical hypodopaminergia with D2R-βarr2 agonism and striatal hyperdopaminergia with D2R-βarr2 antagonism in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%